Scoping review of community health participatory research projects in Ghana - Irene A. Kretchy; Lydia O. Okoibhole; Olutobi Adekunle Sanuade; Hannah Jennings; Daniel Ll Strachan; Ann Blandford; Francis Agyei; Paapa Asante; Olamide Todowede; Mawuli Kushitor; Kafui Adjaye-Gbewonyo; Daniel Arhinful; et al. (Taylor & Francis Group, 2022)
Background Community health participation is an essential tool in health research and management where community members, researchers and other relevant stakeholders contribute to the decision-making processes. Though community participation processes can be complex and challenging, evidence from previous studies have reported significant value of engaging with community in community health projects. Objective To identify the nature and extent of community involvement in community health participatory research (CHPR) projects in Ghana and draw lessons for participatory design of a new project on diabetes intervention in Accra called the Contextual Awareness Response and Evaluation (CARE) diabetes project. Methods A scoping review of relevant publications on CHPR projects in Ghana which had a participatory component was undertaken. PubMed, PsycINFO, African Journal Online, Health Source: Nursing/Academic Edition, Humanities International Complete and Google Scholar were searched for articles published between January 1950 and October 2021. Levac et al.'s (2010) methodological framework for scoping reviews was used to select, collate and characterise the data. Results Fifteen studies were included in this review of CHPR projects from multiple disciplines. Participants included community health workers, patients, caregivers, policymakers, community groups, service users and providers. Based on Pretty's participation typology, several themes were identified in relation to the involvement of participants in the identified studies. The highest levels of participation were found in two studies in the diagnosis, four in the development, five in the implementation and three in the evaluation phases of projects. Community participation across all studies was assessed as low overall. Conclusion This review showed that community participation is essential in the acceptability and feasibility of research projects in Ghana and highlighted community participation's role in the diagnosis, development, implementation and evaluation stages of projects. Lessons from this review will be considered in the development, implementation, and future evaluation of the CARE diabetes project.